Edge coloring of small signed graphs - Robert Janczewski; Krzysztof Turowski; Bartłomiej Wróblewski (TASK Quarterly)
In 2020, Behr introduced the problem of edge coloring of signed graphs and proved that every signed graph (G, sigma) can be colored using Delta(G) or Delta(G) + 1 colors, where Delta(G) denotes the maximum degree of G. Three years later, Janczewski et al. introduced a notion of signed class 1, such that a graph G is of signed class 1 if and only if every signed graph (G, sigma) can be colored using Delta(G) colors.